\(Aristolochia austroyunnanensis\) S. M. Hwang, a new record for the flora of Vietnam - Van The, Pham; Ngoc Bon, Trinh; Thanh Huong, Le Thi; Van Truong, Do (Academia Journal of Biology, 2023)
Aristolochia austroyunnanensis S. M. Hwang (Aristolochiaceae), a species endemic to southern China (Yunnan and Guangxi provinces), is newly recorded for the flora of Vietnam. This newly recorded species belongs to subgenus Siphisia and is most similar to Aristolochia petelotii O. C. Schmidt and A. fangchi C. Wu ex L. D. Chow & S. M. Hwang. Detailed morphological description and color illustrations, together with information on distribution, habitat, phenology, and taxonomic notes are also given.